Integrating proteomics with electrochemistry for identifying kinase biomarkers1. Issue 8 (14th August 2015) - Amit, Einav; Obena, Rofeamor; Wang, Yi-Ting; Zhuravel, Roman; Reyes, Aaron James F.; Elbaz, Shir; Rotem, Dvir; Porath, Danny; Friedler, Assaf; Chen, Yu-Ju; Yitzchaik, Shlomo
<x xml:space="preserve">Abstract</x> We present an integrated approach for highly sensitive identification and validation of substrate-specific kinases as cancer biomarkers.